(untitled) (Physical Education, Health and Social Sciences, 2025)
Context: Akseer-e-Pachish and Pachrin syrup are the two branded herbal medicines marketed widely for their antidiarrheal property. Objectives: This study is focused to investigate the antidiarrheal effect of both products and to provide scientific background for their activity. Material and Methods: Both herbal brands were evaluated against different types of diarrhea induced by castor oil (1 ml/kg), magnesium sulphate (2 mg/kg) and clarithromycin (100 mg/kg) using pigeon model. Charcoal activity was used for determination of changes in GI transit time. Results: Both brands confirmed significant (p<0.001) reduction in average weight of stool. Discussion and conclusion: Significant (p<0.01) decrease in intestinal motility was also noticed for both brands. Conclusion: It was concluded that both herbal medicines have anti-diarrheal effect on the basis of findings.